Las relaciones entre la Iglesia católica y el régimen franquista en la revista religiosa Vida Nueva - Sánchez-Camacho, Jesús (Cauriensia, 2022)
After the Second Vatican Council, the Catholic Church considered revising the 1953 Concordat between the Holy See and Spain. The negotiations for the renewal of these agreements did not remain unnoticed in the society and the Church of that period. The magazine Vida Nueva, specialized in social and religious information, accepts the message of the Council, and tries to implement it in the Spain of that time. For this reason, the negotiation of a new concordat is one of the themes that appears frequently in the editorials of the weekly. This study examines the contents of the relations between the Church and the State in the editorials of this conciliar magazine between 1968 and 1975. The results show the vision of Vida Nueva about the change of the agreements between both institutions. The weekly takes a position in favour of partial negotiations that are easy to revise, opposes the reciprocal privileges between the Church and the Regime, proposes a healthy collaboration and respect between both institutions, suggests a mixed system of financing, expresses its opposition to the privilege of ecclesiastical jurisdiction, and criticizes the fines for homilies and the arrests of priests, which limit the freedom of the Church in its pastoral activity.